2019
DOI: 10.14216/kjco.19018
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for atypical lymph node metastasis in gastric cancer

Abstract: The present study aimed to evaluate atypical lymph node metastasis rates according to tumor depth, size, and location in patients with gastric cancer. Methods: A total of 727 gastric adenocarcinoma patients, with metastasis to 1 or 2 lymph nodes, who underwent radical gastrectomy with curative intent from May 2003 to May 2017, were enrolled in this study. The characteristics of atypical (skip or transversal) metastases were evaluated according to the following risk factors: longitudinal versus circumferential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The control group included 25 males and 25 females, the mean age at diagnosis was 74 years old (range: 37−92 years); 4 patients underwent urgency surgery for occlusive or bleeding disease; 5 patients were subjected to neoadjuvant chemotherapy according to the FLOT regimen. The majority of tumors ( n = 30, 60%) were located in antral region, and were represented by low-grade ( n = 19, 61%) [ 15 ], tubular moderately differentiated adenocarcinoma ( n = 14, 28%) [ 21 ], intestinal type ( n = 18, 36%) according to Lauren [ 23 ], tubular 2 (tub2) ( n = 14, 28%) following JGCA classification [ 24 ]. Six patients suffered from early gastric cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The control group included 25 males and 25 females, the mean age at diagnosis was 74 years old (range: 37−92 years); 4 patients underwent urgency surgery for occlusive or bleeding disease; 5 patients were subjected to neoadjuvant chemotherapy according to the FLOT regimen. The majority of tumors ( n = 30, 60%) were located in antral region, and were represented by low-grade ( n = 19, 61%) [ 15 ], tubular moderately differentiated adenocarcinoma ( n = 14, 28%) [ 21 ], intestinal type ( n = 18, 36%) according to Lauren [ 23 ], tubular 2 (tub2) ( n = 14, 28%) following JGCA classification [ 24 ]. Six patients suffered from early gastric cancer.…”
Section: Resultsmentioning
confidence: 99%
“…11p) [ 14 ]. Many theories have been proposed to explain such an occurrence, most of them dealing with the complex, multidirectional nature of the lymphatic drain of the stomach [ 3 , 13 , 15 ]. It has been demonstrated that patients showing skip metastasis or multiple metastatic stations, especially in the CnLN compartment, experience shorter survival [ 16 ].…”
Section: Introductionmentioning
confidence: 99%